Revitalization of the Kuto Besak Fort in Palembang as an Indonesian Defense Heritage Asset - Francoise, Jeanne (KnE Social Sciences, 2022)
This research investigated the meaning of the revitalization process of colonial forts in Indonesia as defense heritage assets. This was a case study of the revitalization of Kuto Besak Fort in Palembang, South Sumatera. The researchers also analyzed the importance of studying defense heritage in defense diplomacy courses. The aim of this paper was to raise awareness about the defense heritage concept in Indonesia, as well as to create a framework that stakeholders could use to carry out the revitalization process. Qualitative methods were used through a literature review and examining references about the Kuto Besak revitalization process and Palembang history. Three theories were employed: the concept of defense heritage from Dr. Jeanne Francoise, defense diplomacy theory, and the revitalization definition from the Regional Revitalization Guidelines of the Indonesian Ministry of Public Works No.18/PRT/M/2010. It is hoped that this analysis can be used as an academic reference for the South Sumatera government to revitalize Kuto Besak fort, as well as to promote the idea of defense heritage in young people in Palembang, to increase their interest in the defense heritage values behind historical objects or buildings around them. Keywords: Indonesia, defense heritage, Kuto Besak fort, Palembang, South Sumatera, defense diplomacy, historical building, revitalization